(untitled) (Bangladesh Journal of Agricultural Research, 2026)
The study was conducted at the selected weaving areas of shitalpati or cooling mat handicrafts in Bangladesh during 2019-2021 to know the present situation of the handicrafts, existing constraints and formulate policy options for its improvement in the country. Although the traditional art of shitalpati weaving of Bangladesh was recognized as “Intangible Cultural Heritage” by the United Nations Educational, Scientific and Cultural Organization (UNESCO), but presently the glory of the cottage industry is in declining trend due to lack of research and development activities on "murta" plant (Schumannianthus dichotomus L.) cultivation (stem cane of this plant, which is used for shitalpati weaving). Quality murta cane production and processing, and unfair market price of the products, competing with plastic mats, lacking of diversification and value addition of handicrafts, lack of promotional activities of the stakeholders etc. are also responsible. It was observed that the murta plant has wide adaptability that can be cultivated easily in submerged or fallow lands. Murta plant can tolerate salinity and waterlogging environments and prevents soil erosion, which would be an adaptation option under changing climate in Bangladesh. Therefore, policy formulation and suitable action plan (short, medium and long term basis) should be done for recapturing the glory of shitalpati handicrafts in Bangladesh. Bangladesh J. Agril. Res. 48(1): 19-36, March 2023